An underestimated factor for therapeutic decision-making in rare diseases: parents' (un)knowledge—the example of Duchenne muscular dystrophy caregivers and non-invasive ventilation - Eliza Wasilewska; Andrzej Wasilewski; Ewa Pilarska; Jolanta Wierzba; Sylwia Małgorzewicz; Marek Niedoszytko (Orphanet Journal of Rare Diseases)
Abstract Background Duchenne muscular dystrophy (DMD) is a progressive genetic disease that leads to degeneration of muscles, including respiratory muscles, and requires early introduction of non-invasive ventilation (NIV). Parental knowledge and management strategies for pulmonary care are essential when respiratory function is compromised, particularly in conditions involving sleep apnea and the progression of chronic respiratory failure. The aim of this study was to assess parental knowledge of key aspects of pulmonary care in DMD and to identify knowledge gaps that may influence therapeutic decisions. Methods A cross-sectional survey was conducted as part of the multidisciplinary care program for DMD at the Center for Rare Diseases in Gdańsk, accredited by the World Duchenne Organization. The questionnaire assessed (1) demographic and clinical details, (2) pulmonary healthcare practices, (3) understanding of pulmonary rehabilitation, (4) knowledge about NIV, and (5) sources of information on respiratory care. Results The study included 111 parents (F/M 83/28, mean age 45.5 ± 6.75 years) of 111 children with DMD (all male, mean age 11.5 ± 5.45 years; 38% non-ambulatory). The majority of individuals (77.5%) regularly visited a pulmonary specialist with spirometry performed. Most parents reported satisfactory knowledge about respiratory issues in DMD but 77% of them reported insufficient knowledge about NIV (Chi2 = 53.4, df = 12, p = 0.00). Only 11% weren’t afraid to use NIV in the future, while 73% were afraid because of a lack of or inaccurate information. Physicians were the primary source of knowledge for pulmonary care, while the internet and peer experiences were rarely used. Conclusion The majority of parents of children with DMD understand the basics of pulmonary problems. A significant information gap exists concerning advanced respiratory interventions such as non-invasive ventilation (NIV). This leads to anxiety among parents and impairs therapeutic decision-making, delaying appropriate treatment including respiratory support. There is a need for respiratory education programmes for parents and patients, especially as the estimated longer survival time for patients with DMD will make respiratory challenges even more significant. Graphical Abstract